2017
DOI: 10.3389/fmicb.2017.01221
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota of Healthy Chilean Subjects Reveals a High Abundance of the Phylum Verrucomicrobia

Abstract: The gut microbiota is currently recognized as an important factor regulating the homeostasis of the gastrointestinal tract and influencing the energetic metabolism of the host as well as its immune and central nervous systems. Determining the gut microbiota composition of healthy subjects is therefore necessary to establish a baseline allowing the detection of microbiota alterations in pathologic conditions. Accordingly, the aim of this study was to characterize the gut microbiota of healthy Chilean subjects u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
161
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(200 citation statements)
references
References 75 publications
(92 reference statements)
15
161
0
7
Order By: Relevance
“…Lower expression of tight junction protein in vancomycin treated mice caused the increase in gut permeability resulting in the higher cecal index and fluid accumulation of cecal sample. It is reported that increased abundance of Verrucomicrobia causes a decrease in inflammation and enhances glucose metabolism of the host [77][78][79]. On the sixth day of vancomycin treatment, the current results revealed a decrease in Proteobacteria and increase in Verrucomicrobia which might have caused an anti-inflammatory effect in the gut.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Lower expression of tight junction protein in vancomycin treated mice caused the increase in gut permeability resulting in the higher cecal index and fluid accumulation of cecal sample. It is reported that increased abundance of Verrucomicrobia causes a decrease in inflammation and enhances glucose metabolism of the host [77][78][79]. On the sixth day of vancomycin treatment, the current results revealed a decrease in Proteobacteria and increase in Verrucomicrobia which might have caused an anti-inflammatory effect in the gut.…”
Section: Discussionsupporting
confidence: 44%
“…It is well established that overexpression of Inflammatory cytokine like TNFα is associated with the higher gut permeability by suppressing the expression of tight junction proteins like occludin Page | 24 and claudin 1 [77,78]. Lower expression of tight junction protein in vancomycin treated mice caused the increase in gut permeability resulting in the higher cecal index and fluid accumulation of cecal sample.…”
Section: Discussionmentioning
confidence: 99%
“…14 Bacteria belonging to Firmicutes and Bacteroidetes phyla dominate the gut and, to a lesser extent, species from Verrucomicrobia, Proteobacteria, and Actinobacteria ( Figure 1). 15,16 The gut microbiome is important for several functions such as fermentation and absorption of nutrients in the colon, development of the immune system, and intestinal mucosal growth and integrity. 17,18 There is growing evidence that certain groups of bacteria such as Clostridia are important for normal intestinal function and protection against intestinal diseases, whereas other proinflammatory bacteria, specifically certain species belonging to Enterobacteriaceae, are harmful.…”
Section: Human Microbiomementioning
confidence: 99%
“…The gut microbiome becomes relatively stable in adulthood, with its intraindividual variation being lower than the differences seen between different subjects . Bacteria belonging to Firmicutes and Bacteroidetes phyla dominate the gut and, to a lesser extent, species from Verrucomicrobia, Proteobacteria, and Actinobacteria (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…There was a striking loss of Verrucomicrobia, particularly in female mice (Figure 9a, lower panels), which exhibit unexpectedly high levels of these bacteria in the young (d56) control cohort and the d340 female chowfed group. Verrucomicrobia (primarily of the genus Akkermansia) are mucusdegrading commensals that have been reported to be a marker of gut health due to their ability to promote gut barrier integrity, Treg generation and insulin sensitivity 60,61 : thus, these findings may suggest, as with flies 45 , that female C57BL/6J mice may be particularly vulnerable to (HCD-induced) gut pathology during ageing. The failure of ES-62 to restore these commensals, and promote Treg responses in general 9 , may go some way to explaining why the helminth product does not extend lifespan in female HCD-fed mice but only in the male cohorts, which given their lower levels of Verrucomicrobia may be innately less susceptible to the pathological consequences of gut dysfunction.…”
Section: Es-62 Maintains Gut Microbiota Homeostasis During Hcd-inducementioning
confidence: 99%